Psychological violence by an intimate partner: Construction of a screening scale - Teixeira, Monica Gonçalves de Melo (2021)
Psychological abuse has public health implications, given the physical and mental health problems. We propose a 47-item scale, which assists in the screening of psychological abuse, to support clinical and institutional interventions. Participated in the study 99 women from health and education institutions and 27 women treated at a Defense and Community Center for Women (CDCM), in situations of domestic violence and/or social vulnerability. A statistically significant mean difference was observed in the instrument's total score (p<0,05), with good reliability indexes (α=0,95), indicating the content validity of the items in the instrument, which refer to the experience of women in situations of violence and social vulnerability. Further studies are necessary to enable the use of the instrument and the dimensions addressed.